AN ANALYSIS OF TEACHERS’ WAYS IN STIMULATING STUDENTS’ INTEREST IN TEACHING LEARNING PROCESS AT VOCATIONAL HIGH SCHOOL 9 PADANG - Yulmiati, FNU (Universitas PGRI Sumatera Barat, 2018)
The background of this research was the decreasing of students’ interest in the teaching learning process of English which several students tended to make noise, disturb their friends, talk with their friends, be lazy, do daydream, go to toilet many times, and leave the subject. The purpose of this research was to find out and to describe the teachers’ ways in stimulating the students’ interest in the teaching learning process and to find out and to describe the influences of the teachers’ ways toward the students’ interest in the teaching learning process. This research was qualitative research which there was four English teachers as the participants. In gathering data, the researcher did the observation in the participants’ class by using tools such as: camera, observation checklist, and field note and then, the researcher did interview toward the participants by using recoder. Based on the research result, the researchers found that there were 11 teachers’ ways in stimulating students’ interest in teaching learning process. From 11 ways, there were 7 ways based on the theories and 4 ways were found different from the theories. Then, the researcher also found there were some influences of the teachers’ ways toward the students’ interest in teaching learning process. The influences were included from the indicator of characteristics of students’ interest such as attention, concentration, pleasant feeling of applied effort, willingness to learn and information seeking (cognition). For the indicator of information seeking (cognition), the researcher did not find anything teachers’ ways that could stimulate the students in searching the information. The researcher concluded that the teachers at SMKN 9 Padang had different ways in stimulating the students’ interest in the teaching learning process of English which the ways had the difference influences toward the students’ interest in teaching learning process.